A tale of two women: Ishimoto Shidzue and Selma Ekrem, a study on missionary feminism and women's education - Soyubol, Kutluğhan. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2007., 2007)
This study, which starts by taking modernization as its focal point, concentrates on two countries (late Meiji, Taisho and early Showa Japan and late Ottoman Empire, early Republican Turkey) that are accepted as examples of “late modernization.” To do this, it uses two “modern” women, namely Ishimoto Shidzue and Selma Ekrem, from these countries as its main subjects. As a result of the fact that these two women published their autobiographies in America in the 1930s, and appeared in international circles as representatives of their countries, this study puts the biographies of these women, as well as their autobiographies, at its center. In addition to that, it asserts that these two women knew each other through the international feminist networks of the period, and sat next to each other at an international feminist meeting in Chicago in 1933. Furthermore, it tries to show the path that carried these women to their encounter by following the traces of these two women. Thus, arriving at the missionary, feminist and socialist networks of the period, it displays another face of modernization. Moreover, while doing this, it indeed focuses on the different shapes that these women had to get into, and the privileges of the West concerning the East that they sometimes used and sometimes challenged in order to survive in such international networks. Finally, the study succeeds in reading the differing paths of these two “late” modernization examples ii through these two women who differentiated themselves from their societies almost in the same manner in the same period.
Keywords: Women -- Turkey.